2012
DOI: 10.4081/rt.2012.e23
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Giant Pseudoangiomatous Stromal Hyperplasia of the Breast: Magnetic Resonance Imaging Findings

Abstract: Pseudoangiomatous stromal hyperplasia (PASH) of the breast is a benign myofibroblastic process. We present the case of a 17-year-old girl who underwent diagnostic work-up due to an enlargement of her left breast. She was submitted to ultrasounds and magnetic resonance imaging (MRI) which depicted a 14 cm lesion in her left breast. The patient was later operated and histology revealed PASH. Although PASH may range from 0.6–12 cm, a few lesions over 12 cm have been described, the largest being 20 cm. Large serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Our case presents clinically as a bilateral multiple palpable breasts masses with the clinical and radiological assessment coping bilateral multiple fibroadenoma and also MRI findings cope with multiple bilateral lesions with benign criteria however the histo-pathological findings cope with PASH. Yoo cm, but it can also present as an asymmetric appearance of the gland whose size or density increases over time [1]. On our ultrasound they showed bilateral diffuse enlarged breasts with multiple variable sized hypo echoic masses seen scattered inside and this agree with Hargaden et al [5] that say ,PASH has no characteristic appearance, including both its margins and echogenicity.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our case presents clinically as a bilateral multiple palpable breasts masses with the clinical and radiological assessment coping bilateral multiple fibroadenoma and also MRI findings cope with multiple bilateral lesions with benign criteria however the histo-pathological findings cope with PASH. Yoo cm, but it can also present as an asymmetric appearance of the gland whose size or density increases over time [1]. On our ultrasound they showed bilateral diffuse enlarged breasts with multiple variable sized hypo echoic masses seen scattered inside and this agree with Hargaden et al [5] that say ,PASH has no characteristic appearance, including both its margins and echogenicity.…”
Section: Discussionsupporting
confidence: 79%
“…The examination protocol consisted of T1-weighted image (T1WI) (Figure 3), T2-weighted image (T2WI) (Figure 4), short-tau inversion recovery (STIR) and Diffusion weighted imaging were also obtained ( Figure 5), as well as dynamic et al [4] had reported that clinical and radiological findings of PASH resemble those of fibrodenoma and all imaging modalities have no specific features to characterize PASH and distinguish it from other pathologic entities. In asymptomatic patients it usually presents as a breast imaging-reporting and data system (BI-RADS) type 3 lesion, suggesting a probably benign lesion [1]. In our case mammography revealed bilateral enlarged dense breasts with bilateral multiple variable sized masses noted and this agree with Solomou et al [1] stated that say mammography of PASH can reveals single or multiple non-calcified masses, with well circumscribed margins, usually ranging from 1-10 contrast-enhanced magnetic resonance imaging (DCE-MRI) after the administration of gadolinium ( Figure 6).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with mammography and ultrasound, little has been reported on MRI characteristics. No common features have been described and the signal on both T1-and T2weighted images may vary [12]. A MRI is conducted in our patient to assess the lesions and determine their locations.…”
Section: Discussionmentioning
confidence: 99%